Multi-omics Mendelian randomization and machine learning identify candidate therapeutic targets for Alzheimer’s and Parkinson’s diseases - Xun Li; Lei Zhang; Jinyan Xia; Meiling Zheng; Zhipeng Zhou; Jing Cai (Mammalian Genome, 2026)

Oxygen-adaptive continuous lactate monitoring via dual-regime electrochemical sensing and dynamic calibration strategy - Xinyi Wang; Yuying Lin; Rubing Xiong; Jing Liu; Yue Liu; Zijie Li; Yongmei Chen; Yong Xia; Zhiqi Li; Lei Mou; Meiling Liu (Analytica Chimica Acta, 2026)

Integrated biochar-iron amendment mitigates rice cadmium uptake via soil immobilization, iron plaque barriers, and microbial community restructuring - Meiling Xu; Tianyi Hu; Fangge Xu; Jing Che; Guobing Wang; Yepu Li; Qiao Xu; Xiaozhi Wang (Journal of Environmental Chemical Engineering, 2026)

Chemical reaction driven interfacial reconstruction of In2O3/S-BiOCl heterojunction with Ag2S quantum dots enables a self-validated fluorescence/photoelectrochemical dual mode nitrite sensing - Jingshu Li; Yuee Zhong; Manqi Li; Jiawei Zhou; Hengwen Tang; Jing Liu; Jianru Tang; Xiaohua Zhu; Youyu Zhang; Meiling Liu (Analytica Chimica Acta, 2026)

TRPV4/IP3R-1-mediated endothelial pyroptosis drives pulmonary microvascular endothelial permeability in endotoxin-induced acute lung injury - Shasha Liu; Shuan Dong; Lirong Gong; Jing Yang; Huayang Liu; Meiling Piao; Ya Wu; Huirong An; Li Zhang; Jianbo Yu (Inflammation Research, 2026)

Co-exposure to PS-NPs and HFPO-TA potentiates reproductive toxicity via ferroptosis and SLC1A5-Mediated glutamine deprivation in male mice - Lihai Wu; Jing Ding; Jiayu Xue; Meiling Le; Yiqi Wan; Wanting Zhao; Yangyang Yuan; Xiaodong Kuang; Xinyuan zhao; Liping Zheng; Dalei Zhang (Chemico-Biological Interactions, 2026)

Design and Performance Evaluation of Amino Acid-Decorated UiO-66-NH2/Pebax Mixed Matrix Membranes for Efficient CO2 Separation - Xiaochun Jing; Wei Zhao; Pengzhi Bei; Hongjing Liu; Yan Dai; Xu Zhao; Chengpeng Zhang; Meiling Shi; Ying Zhang (Water, Air, & Soil Pollution, 2026)

Multifunctional metallized basalt/PA6 composites: EMI shielding, joule heating, and tunable rigidity - Jiajun Du; Hao Shi; Xin Wang; Meiling Xiang; Jing Zhang (Chemical Engineering Journal, 2026)

Pore Structure Characteristics and Controlling Factors of Different Lithofacies in Lacustrine Shale: A Case Study of Fengcheng Formation in Mahu Sag, Junggar Basin - Jiahao Lyu; Fujie Jiang; Jing Xue; Tao Hu; Yuping Wu; Chenxi Zhang; Meiling Hu; Renda Huang (Journal of Earth Science, 2026)

Ecological distribution and functional characterization of polyethylene-degrading enzymes from diverse metagenomes - Ning Wang; Meiling Jin; Zixuan Zhu; Yuxin Wang; Xinyu Li; Jing Xu; Shijunyi Cheng; Yuanying Zhu; Ruiqi Wang; Tong Xu; Furong Yin; Xinyue Li; et al. (Science of The Total Environment, 2026)

Grass-legume mixture optimizes soil new carbon sequestration by leveraging microbial necromass dynamics in a pear orchard - Qiao Xu; Yingdong Zhao; Meiling Xu; Jinlong Dong; Weiqin Yin; Jing Ma; Xiaozhi Wang (Agriculture, Ecosystems & Environment, 2025)

Nanoplastics in infusion system remains underexplored: Evidence from detected nanoplastics in hospital-sourced infusion products - Licheng Wang; Jing Peng; William Ji; Muhammad Ali Tahir; Jilun Wang; Tao Wang; Meiling Weng; Liwu Zhang (Journal of Hazardous Materials, 2025)

Wheat yield prediction using an enhanced WOFOST with soil stratified hydrothermal module driven by GLASS and ERA5-land products over Yellow River Basin - Jing Zhang; Guijun Yang; Meiling Gao; Lijie Zhang; Weinan Chen; Miao Liu; Youming Zhang; Aohua Tang; Zhenhong Li (Computers and Electronics in Agriculture, 2025)

Hierarchically superhydrophobic ceramic fiber membrane with thermal-induced pore modulation for antifouling oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Huaiyuan Wang (Chemical Engineering Journal, 2025)

Different responses of cyanobacterial communities to climate change and anthropogenic activities revealed by the 500-year sedimentary record of Lake Daihai - Jing Wang; Hai Xu; Jianghu Lan; Kang’en Zhou; Yunping Song; Jin Zhang; Meiling Yang; Baoli Wang (Anthropocene, 2025)

Development of the novel formulations of perospirone for the treatment of schizophrenia - Zijun Zhang; Famin Ke; Jili Wu; Xiyao Li; Xin Chen; Lanxing Zhang; Pei Jing; Zerong Liu; Zhongbing Liu; Ruilin Lu; Shihua Fu; Meiling Zhou; et al. (Drug Delivery and Translational Research, 2025)

Multi-residue analytical method development and dietary exposure risk assessment of 345 pesticides in mango by LC-Q-TOF/MS - Xingqiang Wu; Jianxun Li; Jing Wei; Kaixuan Tong; Yujie Xie; Qiaoying Chang; Xiaoxuan Yu; Bei Li; Meiling Lu; Chunlin Fan; Hui Chen (Food Control, 2025)

Estimation of winter wheat yield by assimilating MODIS LAI and VIC optimized soil moisture into the WOFOST model - Jing Zhang; Guijun Yang; Junhua Kang; Dongli Wu; Zhenhong Li; Weinan Chen; Meiling Gao; Yue Yang; Aohua Tang; Yang Meng; Zhihui Wang (European Journal of Agronomy, 2025)

Ultrastable Ti@Ir core-shell catalyst with low iridium loading for water electrolysis at industrial-level current density - Jiahao Yang; Zhaoping Shi; Yibo Wang; Hongxiang Wu; Jing Ni; Pengbo Wang; Meiling Xiao; Changpeng Liu; Wei Xing (Chemical Engineering Journal, 2025)

Similarity recognition approach to identify zero-added MSG soy sauce using stable isotopes and amino acid profiles - Chunlin Li; Meiling Sheng; Menglin Zhang; Karyne M. Rogers; Jing Nie; Shengzhi Shao; Jianbo Xiao; Yuwei Yuan (Food Chemistry, 2024)

Bacteria contribute more than fungi to SOC decomposition in a paddy field under long-term free-air CO2 enrichment - Meiling Xu; Feifan Zhang; Ling Zhang; Hongze Zhang; Caixian Tang; Xiaozhi Wang; Jing Ma; Qiao Xu (European Journal of Soil Biology, 2024)

Interfacial charge demulsification endowed dual-network photocatalytic hydrogen-bonded PVA@agarose membranes for oil-water separation - Jing Jing; Zhanjian Liu; Yuxin Fu; Haonan Liu; Xiguang Zhang; Meiling Li; Liyan Liu; Huaiyuan Wang (Journal of Hazardous Materials, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Novel superhydrophobic sponge with flower-like architecture for oily emulsion separation and organic pollutants photodegradation - Jinyue Yang; Zhanjian Liu; Jing Jing; Xiguang Zhang; Yuxin Fu; Meiling Li; Huaiyuan Wang (Journal of Environmental Chemical Engineering, 2024)

Embryonic development and transcriptomic analysis in red-eared slider Trachemys scripta elegans under salinity stress - Jing Lin; Yuchen Kong; Haitao Shi; Meiling Hong; Li Ding (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

Minocycline attenuates the bilirubin-induced developmental neurotoxicity through the regulation of innate immunity and oxidative stress in zebrafish embryos - Guanghua Xiong; Tianle Hu; Yihong Yang; Haiyan Zhang; Meiling Han; Jiahao Wang; Yipeng Jing; Hongbo Liu; Xinjun Liao; Yong Liu (Toxicology and Applied Pharmacology, 2024)

Illuminated fulvic acid stimulates denitrification and As(III) immobilization in flooded paddy soils via an enhanced biophotoelectrochemical pathway - Yanqiong Zeng; Honghui Wang; Jiehua Hu; Jing Zhang; Feng Wang; Tongyu Wang; Qiqi Zhou; Randy A. Dahlgren; Meiling Gao; Hui Gao; Zheng Chen (Science of The Total Environment, 2024)

Morphological and transcriptomic analyses of embryonic development of red-eared slider Trachemys scripta elegans - Jing Lin; Miaomiao Zhang; Fangbin Liang; Yunfang Ni; Jiani Zhang; Haitao Shi; Meiling Hong; Li Ding (Animal Reproduction Science, 2024)

In situ formation of fluorescence species for the detection of alkaline phosphatase and organophosphorus pesticide via the ascorbate oxidase mimetic activity of AgPd bimetallic nanoflowers - Luo Luo; Jing Liu; Yani Liu; Haoyu Chen; Youyu Zhang; Meiling Liu; Shouzhuo Yao (Food Chemistry, 2024)

Scalable fabrication of a robust asymmetric superwetting Janus mesh by facile spray-coating for oil–water emulsions separation - Jing Jing; Zhanjian Liu; Xiguang Zhang; Jinyue Yang; Meiling Li; Ruixia Yuan; Guolin Jing; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Nanocomposite hydrogel to deliver the immunomodulator lenalidomide and anti-inflammatory hesperidin locally to joints affected by rheumatoid arthritis - Xingjie Du; Yan Lin; Zheyu Shuai; Junfeng Duan; Changguang Wang; Junsheng Liu; Jun Jiang; Jianming Wu; Meiling Zhou; Zhirong Zhang; Zhongbing Liu; Xiangyu Zhou; et al. (Chemical Engineering Journal, 2023)

Metabolic profiling of Apostichopus japonicus body wall exposed to a typical type of PBDEs: potential health risks and impact on sea cucumber health - Kui Ding; Pengji Zhuo; Meiling Ge; Xiaomei Liao; Jing Mo; Shilin Liu; Qinzeng Xu; Xuelei Zhang (Frontiers in Marine Science, 2023)
Introduction Sea cucumbers are cultivated mainly for their valuable body wall. Polybrominated diphenyl ethers are common persistent pollutants in sea waters with known impacts on aquatic animals nonetheless not yet studied for the body wall of sea cucumbers. Methods Using ltra-high performance liquid chromatography-quadrupole time-of-flight mass spectrometry (UPLC-Triple-TOF-MS), we investigated the metabolic impact of 2,2',4,4'-tetrabromodiphenyl ether (BDE-47) on the body wall of Apostichopus japonicus . etabolite changes and metabolic pathway alterations were assessed in response to three distinct concentrations of BDE-47: 0.1 µg/L, 1.0 µg/L, and 10.0 µg/L. REsults Exposure to BDE-47 led to notable alterations in the metabolic profiles of the body wall. A total of 95~102 metabolites in the 0.1 ~ 10.0 µg/L BDE-47 treated group were altered significantly, and various disrupted metabolic pathways were identified and characterized. These metabolites and metabolic pathways were mainly involved in lipid metabolism, energy metabolism, immunity, oxidative stress, inflammation, and neurotoxicity. Discussion The findings of our study shed light on the potential health risks that polybrominated diphenyl ethers present to sea cucumbers. This underscores the imperative for both researchers and policymakers to delve deeper into further investigations and studies. These results indicate the necessity for enhanced monitoring and management practices within the sea cucumber aquaculture industry to mitigate the impact of these persistent organic pollutants and protect the health and safety of this valuable resource.

Development and Characterization of Multifunctional Wound Dressing with the Property of Anti-bacteria and Angiogenesis - Xi He; Meiling Zhou; Xuemei Chen; Jing Wang; Xiaoli Zhao; Yanxia Zhu; Tao Liu (Probiotics and Antimicrobial Proteins, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

Neuroplasticity Following Stroke from a Functional Laterality Perspective: A fNIRS Study - Ying Song; ZhiFang Sun; WeiZhen Sun; MeiLing Luo; YiJun Du; Jing Jing; YongHui Wang (Brain Topography, 2023)

Long-term effect of intermediate particulate matter (PM1–2.5) on incident asthma among middle-aged and elderly adults: A national population-based longitudinal study - Shuting Li; Jing Wei; Yaoyu Hu; Yuhong Liu; Meiling Hu; Yadi Shi; Yongxi Xue; Mengmeng Liu; Wenhan Xie; Xiuhua Guo; Xiangtong Liu (Science of The Total Environment, 2023)

High-throughput sequencing reveals tuber mustard genes responsive to Plasmodiophora brassicae in the early stage of infection - Zhaoming Cai; Meiqin Xiang; Jing Tan; Chunhong Cheng; Ying Liu; Jiayu Shi; Meiling Shi; Jin Li; Diandong Wang (Physiological and Molecular Plant Pathology, 2023)

Long-term effect of submicronic particulate matter (PM1) and intermodal particulate matter (PM1-2.5) on incident dyslipidemia in China: A nationwide 5-year cohort study - Meiling Hu; Jing Wei; Yaoyu Hu; Xiuhua Guo; Zhiwei Li; Yuhong Liu; Shuting Li; Yongxi Xue; Yuan Li; Mengmeng Liu; Lei Wang; Xiangtong Liu (Environmental Research, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Adaptive biomineralization in two morphotypes of Sternaspidae (Annelida) from the Northern China Seas - Meiling Ge; Jing Mo; Jack Chi-Ho Ip; Yixuan Li; Wenge Shi; Zongling Wang; Xuelei Zhang; Qinzeng Xu (Frontiers in Marine Science, 2022)
Polychaetes are segmented annelid worms that play a key role in biomineralization in modern oceans. However, little is known about the underlying processes and evolutionary mechanisms. The ventro-caudal shield of Sternaspidae is a typical phosphate biomineral in annelids. Here, we investigated two sternaspids from the northern China Seas, Sternaspis chinensis and Sternaspis liui syn. n, which evolved diverse shield characteristics as local adaptation. Genetic distances, phylogenetic analyses of nuclear markers ( 18S and 28S genes), and mitochondrial genomes revealed that the latter is a junior synonym of the former. The integration of elemental composition and the transcriptomic analysis provided insights into phenotypic shield differences. The electron probe microanalysis showed that shields in S. chinensis were more biomineralized (i.e., with higher iron, phosphorus, and calcium contents) than those in S. liui syn. n. Transcriptomes of the body wall around shields determined 17,751 differentially expressed genes (DEGs) in two morphotypes of the synonymous species. Function enrichment analysis of DEGs showed that S. chinensis has an enrichment of the putative biomineralization pathways (i.e., ion transport and calmodulin binding), while S. liui syn. n consumed more energy and produced more proteins (i.e., oxidative phosphorylation and ribosome). DEGs allowed to identify seven shell matrix proteins expressed differentially in the two morphotypes, especially calponin, filamin, chitinase, and protease inhibitor BPTI/kunitz, which might contribute to shield evolutionary plasticity response to their living habitats. Overall, this study 1) revealed an environmental biomineralization adaptation in two polychaete morphotypes of one species by integrating shield chemical composition of shields and transcriptome analyses and 2) provided insights into the molecular mechanisms underlying polychaete biomineralization.

Metatranscriptomic analysis of host response and vaginal microbiome of patients with severe COVID-19 - Meng Xiao; Bo Lu; Rui Ding; Xia Liu; Xian Wu; Yaqian Li; Xudong Liu; Lin Qiu; Zhibo Zhang; Jing Xie; Yu Chen; Dong Zhang; et al. (Science China Life Sciences, 2022)

Brain Dicer1 Is Down-Regulated in a Mouse Model of Alzheimer’s Disease Via Aβ42-Induced Repression of Nuclear Factor Erythroid 2-Related Factor 2 - Yan Wang; Meiling Lian; Jing Zhou; Shengzhou Wu (Molecular Neurobiology, 2020)

Analysis of flavonoids and anthocyanin biosynthesis-related genes expression reveals the mechanism of petal color fading of Malus hupehensis (Rosaceae) - Meiling Han; Chen Yang; Jing Zhou; Jiabin Zhu; Jiaxin Meng; Ting Shen; Zhuanxia Xin; Houhua Li (Brazilian Journal of Botany, 2020)

Investigation of Lactic Acid Bacteria Isolated from Giant Panda Feces for Potential Probiotics In Vitro - Qian Liu; Xueqin Ni; Qiang Wang; Zhirong Peng; Lili Niu; Meiling Xie; Yicen Lin; Yi Zhou; Hao Sun; Kangcheng Pan; Bo Jing; Dong Zeng (Probiotics and Antimicrobial Proteins, 2019)

Clonidine Protects Against Neurotoxicity Induced by Sevoflurane Through NF-κB Signaling Inhibition and Proinflammatory Cytokine Release in Rats - Lian Guo; Yi Yu; Naixing Xin; Jing Sun; Yong Chen; Meiling Yu (Journal of Molecular Neuroscience, 2018)

Assessment of debris inputs from land into the river in the Three Gorges Reservoir Area, China - Jing Wan; Yonggui Wang; Meiling Cheng; Bernard A. Engel; Wanshun Zhang; Hong Peng (Environmental Science and Pollution Research, 2018)

A numerical study of the generation mechanism of internal solitary waves in the Luzon Strait - Jing Wang; Meiling Sun; Xudong Zhang; Lina Sun; Junmin Meng (Acta Oceanologica Sinica, 2015)

Allosteric therapies for lung cancer - Ye Ling; Meiling Jing; Xiang-dong Wang (Cancer and Metastasis Reviews, 2015)

Steroid 5-alpha-reductase type 2 (SRD5A2) V89L and A49T polymorphisms and sporadic prostate cancer risk: a meta-analysis - Qiaoxin Li; Yao Zhu; Jing He; Mengyun Wang; Meiling Zhu; Tingyan Shi; Lixin Qiu; Dingwei Ye; Qingyi Wei (Molecular Biology Reports, 2013)

Development of a real-time RT-PCR method for rapid detection of H9 avian influenza virus in the air - Jing Lv; Baozhi Wei; Tongjie Chai; Xianzhu Xia; Zengmin Miao; Meiling Yao; Yuwei Gao; Rong Huang; Huili Yang; Uwe Roesler (Archives of Virology, 2011)